Studi Hasil Bimbingan Teknis Pengembangan Perangkat Pembelajaran Berbasis Keterampilan Abad-21 dalam Rangka Penerapan Program Merdeka Belajar - Silvi Yulia Sari; Putri Dwi Sundari; Fadhila Ulfa Jhora; Hidayati Hidayati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
The education process in schools should be able to increase mastery of science and technology and provide training and science process skills that can improve the quality of human resources. Education is the main key to modernization and progress for a nation. In reality, 4C learning on 21st century skills has not been fulfilled properly. This needs to be addressed starting by developing a learning material such as lesson plans. The objective of assisting is to improve the competency of teachers in writing lesson plans. The target of the assisting activity was the teachers in SMPN 2 Baso, Agam district. Methods in assisting include presentation and discussion, group work, independent task, and task presentation. Instruments to collect the data consist of knowledge test. Data analysis techniques were descriptive statistical analysis and paired sample t-test. The result of this assisting is the implementation of assisting on the writing of lesson plan is effective to improve the 21st century skills and independent learning program in the school of teachers.